DIGITAL LITERACY IN USING GEOGEBRA LEARNING MEDIA IN TERMS OF SELF-DIRECTED LEARNING - Hasyim, Maylita; Kurniawati, Henny Fathul (MaPan : Jurnal Matematika dan Pembelajaran, 2021)
Digital literacy is important to improve the quality of education, especially in mathematics learning which can develop and engage students in exploring the efficient digital world for learning mathematics. The purpose of this study is to analyze the digital literacy of grade VIII students of SMP Negeri 1 Karangrejo in using GeoGebra learning media in terms of self-directed learning. This type of research is descriptive qualitative. The subjects of this study consisted of six students, and the instruments used were lesson plans, self-directed learning questionnaires, student response questionnaires, and interview guidelines. The result of this research shows that digital literacy with students who have high level for self-directed learning are able to fulfill all of indicators for digital literacy including being able to understand instructions for use and how to use the GeoGebra application, explain the information in the GeoGebra application, do the exercises correctly, participate in exchanging ideas with friends and develop their creativity into a new work in the GeoGebra application, students with moderate self-directed learning are only able to meet five digital literacy indicators including being able to understand instructions for use and explain the information in the GeoGebra application, do the exercises correctly, participate in brainstorming with friends and try to develop their creativity into a new work on the GeoGebra application, and students with low self-directed learning are only able to meet two digital literacy indicators including able to understand the instructions for use and be able to do practice questions correctly.